2019–2020 Florida Citrus Production Guide: Food Safety Requirements and Considerations for the Florida Citrus Grower - Travis K. Chapin; Michelle D. Danyluk; Renée M. Goodrich-Schneider; Keith R. Schneider; Matt Krug; Mark A. Ritenour; Tripti Vashisth (EDIS)
This 8-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. The objective of this document is to present general GAPs principles and PSR requirements needed to plan, execute, and document production practices that will prevent, minimize, or eliminate the possibility of fruit contamination. The materials contained in this document are a combination of recommendations based on the best available science and minimum standards outlined in the PSR. The distinction between voluntary GAPs recommendations and PSR requirements is made in this document by the deliberate use of the words “must” and “should” where “must” is used to denote PSR requirements and “should” is used to denote voluntary GAPs. This document will be reviewed and updated as new risk data emerges and as the Produce Safety Rule guidance is released from FDA; this is not a comprehensive list of all PSR requirements. Written by Travis K. Chapin, Michelle D. Danyluk, Renee M. Goodrich-Schneider, Keith R. Schneider, Matt Krug, Mark A. Ritenour, and Tripti Vashisth, and publsihed by the Agronomy Department, March 2019.